Autophagy is required for sulfur dioxide tolerance in Saccharomyces cerevisiae. Issue 2 (22nd October 2019) - Valero, Eva; Tronchoni, Jordi; Morales, Pilar; Gonzalez, Ramon
Summary: Sulfiting agents are among the most widely used preservatives in the food and beverages industries, including winemaking, and one of their main functions is inhibition of spoilage microorganisms. We have used a whole genome quantitative fitness analysis in order to improve our knowledge on yeast tolerance to sulfites. Apart from the contribution of sulfite efflux to tolerance, results point to vesicle‐mediated transport, autophagy and vacuolar activity as the main cellular functions required to survive sulfite challenges. The involvement of autophagic and vacuolar functions in sulfite tolerance was further confirmed by pairwise competition using a newly constructed atg2 ‐defective strain, as well as by showing induction of ATG8 expression by sulfite. Autophagy is required for the turnover of proteins and subcellular structures damaged by sulfite. In addition, the requirement for vacuolar functions might be related to its role in intracellular pH homeostasis. Finally, the involvement of the sulfite pump Ssu1 and the transcription factor Fzf1 in sulfite tolerance by Saccharomyces cerevisiae was confirmed; a result that validates the experimental approach used in this work. These findings have relevance for understanding sulfite toxicity and tolerance, as well as for the eventual design of strategies aiming to control yeast spoilage. Abstract : We have used a whole genome quantitative fitness analysis in order to improve our knowledge on yeast tolerance to sulfites (used as preservative agents in the food industry). Apart from the contribution to tolerance of sulfite efflux, results point to vesicle‐mediated transport, autophagy, and vacuolar activity as the main cellular functions required to survive sulfite challenges. The finding was further confirmed by pairwise competition using a newly constructed atg2 defective stain, as well as by showing induction of ATG8 expression by sulfite.